Identifying and assessing views among physically-active adult gym members in Israel on dietary supplements - Inbal Druker; Anat Gesser-Edelsburg (Taylor & Francis Group, 2017)
Background Sports dietary supplements are available for sale in public places including sports clubs. Although there is uncertainty regarding their safety, many gym members who regularly work out consume them. The present study aimed to identify the approaches and perspectives of the public who work out in gyms and take dietary supplements. It examined how professionals view sports dietary supplement consumption, and how they communicate this issue to gym members. The literature discusses the prevalence of SDS use among athletes, but rarely discusses or compares between the risk perceptions of gym members, trainers, and dietitians, who represent the physically-active general public, regarding SDS. Methods We conducted constructivist qualitative research in semi-structured one-on-one interviews (n = 34). We held in-depth interviews (n = 20) with a heterogeneous population of adult gym members who take dietary supplements, and (n = 14) with dietitians and fitness trainers. Results The main finding was a gap in risk perception of dietary supplement use between dietitians, gym members and fitness trainers. There was low risk perception among dietary supplements consumers. Trainers believed that benefits of supplement consumption exceeded risk, and therefore they did not convey a message to their clients about risk. In contrast, dietitians interviewed for this study renounced general use of sports dietary supplements and doubted whether trainers had proper nutritional knowledge to support it. Conclusion Lack of awareness of risks suggests that there is a need for communication on this issue. We recommend that professionals (physicians and dietitians) be present in sports clubs that sell such products in an uncontrolled way.